RP-HPLC QUANTIFIABLE TECHNIQUE DEVELOPMENT FOR EVALUATING PREGABALIN AND ETORICOXIB COMBINATION IN TABLET AND BULK KINDS - PUSHPA, M. S. SWARNA; RAJESWARI, T. RAJA (International Journal of Applied Pharmaceutics, 2021)
Objective: This evaluation study aims to initiate a relatively sensitive RP-HPLC quantifiable technique for evaluating pregabalin (PRBN) and etoricoxib (ETRB) combination in tablet and bulk kinds. Methods: PRBN and ETRB chromatographic evaluations were carried off using the “KNAUER C18 Eurospher II column (250 mm × 4.6 mm × 5 μ)”. The mobile phase (MBP) was driven into the KNAUER C18 Eurospher II column at a 1.0 ml/min run rate with an isocratic elution programme of 65% volume of 0.5 mmol sodium perchlorate 35% volume methanol, detected and evaluated the PRBN and ETRB content at 217 nm. Results: The analysis of PRBN and ETRB is executed inside a run period of 15 min. The RP-HPLC quantifiable technique was developed to separate PRBN and ETRB and likely degradants formed from stress testing by isocratic elution. The RP-HPLC quantifiable technique developed was successfully validated to existing ICH limit guidelines and was confirmed as robust, specific, accurate, selective, precise, sensitive, and linear. Conclusion: The RP-HPLC quantifiable technique developed here is more valuable and worthy for routine PRBN and ETRB analysis of tablets and bulk kinds.